PENERAPAN PENDEKATAN KETERAMPILAN PROSES UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS DAN PRESTASI BELAJAR - Kristina Noviyanti Hariyani (DIADIK, 2024)
This study aims to describe the application of process skills approach to increase student’s critical thinking skills and learning achievement in the first grader on informatics subject at SMA Negeri 4 Lahat. The research design used was classroom action research and quasi-experimental design. The research subjects were first grader on informatics subject at SMA Negeri 4 Lahat of the 2022/2023 school year. Purposive sampling was used to determine the quasi-experimental sample, they were X MIPA 2 class as experiment class and X MIPA 5 of SMA Negeri 4 Lahat as control class. The research instrument used observation sheets and tests.The research data were analyzed using descriptive statistics, mean (mean), percentage, and t-test.The results showed that the application of process skills approach, one of approach learning could increase the critical thinking skills and learning achievement of the first grade students of SMA Negeri 4 Lahat